2022
DOI: 10.2478/jccm-2021-0044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of COVID-19 Acute Respiratory Distress Syndrome Patients Requiring Invasive Mechanical Ventilation in a Lower Middle-Income Country

Abstract: Background COVID-19 related acute respiratory distress syndrome (ARDS) requires intensive care, which is highly expensive in lower-income countries. Outcomes of COVID-19 patients requiring invasive mechanical ventilation in Pakistan have not been widely reported. Identifying factors forecasting outcomes will help decide optimal care levels and prioritise resources. Methods A single-centre, retrospective study on COVID-19 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Ejaz et al [11] reported a high mortality rate in COVID-19 related acute respiratory distress syndrome (ARDS). The severity and the likelihood of developing ARDS and related adverse outcomes are linked with different factors including age more than 60 years, male sex, obesity, hypertension, diabetes mellitus, previous lung disease, and specific parameters such as low lymphocyte count and high D-dimer levels [12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…Ejaz et al [11] reported a high mortality rate in COVID-19 related acute respiratory distress syndrome (ARDS). The severity and the likelihood of developing ARDS and related adverse outcomes are linked with different factors including age more than 60 years, male sex, obesity, hypertension, diabetes mellitus, previous lung disease, and specific parameters such as low lymphocyte count and high D-dimer levels [12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…[3] Due to the expanding range of indications for ECMO, its application has been enhanced in the intensive care unit as well as during emergency departments, operating rooms, cardiac catheterization laboratories, and interhospital transfers. [4] The patients who use ECMO generally have inflammatory hemodynamic abnormalities, inflammation, and pathophysiological abnormalities of various organs, which puts them at high risk of other organ failure. [4] The term "hyperthyroidism" is strange within the context of respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Patients on ECMO support have inflammatory, hemodynamic, and pathophysiological abnormalities, which put them at risk for potential complications. [4] According to current literature, 20% to 100% of ECMO acute renal injury (AKI) patients receive renal replacement therapy (RRT) before or during ECMO support. Approximately 85% of patients suffer from AKI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute respiratory distress syndrome (ARDS) is the most common pulmonary complication in critically ill patients that often results in unfavorable outcomes. Approximately two out of five patients with ARDS die [ 1 ], and the recent COVID-19 pandemic taught us that outcome of patients with ARDS due to infectious causes has not changed over recent years [ 2 , 3 ], despite significant improvements in ventilatory management and various other aspects of care for critically ill ARDS patients.…”
Section: Introductionmentioning
confidence: 99%